2019
DOI: 10.3390/app9081619
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Impeller-Vaned Diffuser Interaction in a Centrifugal Compressor

Abstract: The work presents the results of a CFD campaign to investigate the impeller–diffuser interaction in a centrifugal compressor, taking advantage of experimental data from the open literature. Previous studies on the same turbomachine focused on an experimental investigation to understand the flow interaction between the impeller and the vaned diffuser. These experimental data have been used to validate the simulation approach and discuss its results. Several CFD models with increasing complexity have been develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…where n could represent the number of stall cells in the present case; ω = ω real − iσ , the real and imaginary parts represent the angular frequency and growth rate of the instability, respectively. By substituting Equation (11) and Equation ( 12) into Equations (6-10), the governing equations of the unsteady flow field are as follows:…”
Section: Analysis Of the Propagation Velocity Coefficient Kmentioning
confidence: 99%
See 1 more Smart Citation
“…where n could represent the number of stall cells in the present case; ω = ω real − iσ , the real and imaginary parts represent the angular frequency and growth rate of the instability, respectively. By substituting Equation (11) and Equation ( 12) into Equations (6-10), the governing equations of the unsteady flow field are as follows:…”
Section: Analysis Of the Propagation Velocity Coefficient Kmentioning
confidence: 99%
“…Carretta et al [10] adopted a stability parameter (SP) to predict the stability limit; the contribution of each component to the compressor stability was specifically analyzed, and the results showed that the vaned diffuser was responsible for the compressor instability. Bardelli et al [11] investigated the flow in the centrifugal stage of a compressor by different CFD models; unsteady phenomena captured by steady and unsteady simulations have been carefully compared with experimental data in the available literature. Among the instabilities in compressors, one unsteady flow phenomenon, which is known as a rotating stall, has been reported in both centrifugal [12][13][14] and axial [15][16][17][18] compressors.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, surge prevention in gas turbinebased advanced cycles is an important aspect to be investigated from both an academic and an industrial point of view because vibrations due to surge can damage plant mechanical components [18]. Regarding surge subject, the authors suggest C. Cravero's Computational Fluid Dynamics papers [19,20], G.L. Arnulfi's experimental and numerical works [21,22] and E.M. Greitzer's works [23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the addition of short blades indirectly increases the number of blades in the middle and rear sections of the impeller, and enhances the ability of the blade to shear bubbles and the pump to work; the use of short blades can smash the remaining bubbles and discharge them out of the pump [19]. Otherwise, this paper also refers to the research results of other scholars for the centrifugal compressor [20,21].…”
Section: Introductionmentioning
confidence: 99%